Modulatory effects of catechin hydrate against genotoxicity, oxidative stress, inflammation and apoptosis induced by benzo(a)pyrene in mice. (June 2016) - Shahid, Ayaz; Ali, Rashid; Ali, Nemat; Hasan, Syed Kazim; Bernwal, Preeti; Afzal, Shekh Mohammad; Vafa, Abul; Sultana, Sarwat
Abstract: Benzo(a)pyrene [B(a)P], a polycyclic aromatic hydrocarbon (PAH) is a strong mutagen and potent carcinogen. The aim of the present study was to investigate the efficacy of catechin hydrate against B(a)P induced genotoxicity, oxidative stress, inflammation, apoptosis and to explore its underlying molecular mechanisms in the lungs of Swiss albino mice. Administration of B(a)P (125 mg/kg b. wt., p. o.) increased the activities of toxicity markers such as LPO, LDH and B(a)P metabolizing enzymes [NADPH–cytochrome P450 reductase (CYPOR) and microsomal epoxide hydrolase (mEH)] with subsequent decrease in the activities of tissue anti-oxidant armory (SOD, CAT, GPx, GR, GST, QR and GSH). It also caused DNA damage and activation of apoptotic and inflammatory pathway by upregulation of TNF-α, IL-6, NF-kB, COX-2, p53, bax, caspase-3 and down regulating Bcl-2. However, pre-treatment with catechin at a dose of 20 and 40 mg/kg significantly decreased LDH, LPO, B(a)P metabolizing enzymes and increased anti-oxidant armory as well as regulated apoptosis and inflammation in lungs. Histological results also supported the protective effects of catechin. The findings of the present studies suggested that catechin as an effective natural product attenuates B(a)P induced lung toxicity. Highlights: Catechin protects against genotoxicity by modulating CYPOR and mEH enzymes. Genotoxicity, oxidative stress, inflammation and apoptosis may be the plausible mechanisms behind benzo(a)pyrene-induced toxicity. Role of catechin hydrate in suppressing histopathological changes induced by benzo(a)pyrene. Catechin hydrate increased activities of tissue anti-oxidant armory (SOD, CAT, GPx, GR, GST, QR and GSH).